Development and Validation of UNSIL Basketball Guide (PUBbG) Applications Based on Android - Iman Rubiana; Budi Indrawan; Arief Abdul Malik (JUARA : Jurnal Olahraga, 2022)
This research aims to develop and validate the Android-based Unsil Basketball Guide (PUBbG) application. The method used in this research is the Research and Development method. Three experts were involved in validating the design and feasibility of the android application made and user validation by 66 students using the proportional random sampling technique. The instruments used are media and material expert validation instruments and user validation instruments using the System Usability Scale (SUS). Data were analyzed using descriptive statistical techniques. The results showed that the overall application validity test results obtained percentages of 84%, 80%, and 90%, which means that the developed application is valid and feasible to use. The results of user validity using the SUS score are in the excellent category with a value of 72.95, and the results of the application effectiveness assessment based on a user survey get 8.68 results, which means that the application is practical to be able to improve the basic techniques of Bolabakset. This study concludes that the application product that has been made is in the appropriate category based on the results of expert evaluations and is effective for improving basic basketball techniques based on survey results to users.